2021
DOI: 10.48550/arxiv.2109.01405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum superposition of spacetimes obeys Einstein's Equivalence Principle

Flaminia Giacomini,
Časlav Brukner

Abstract: We challenge the view that there is a basic conflict between the fundamental principles of Quantum Theory and General Relativity, and in particular the fact that a superposition of massive bodies would lead to a violation of the Equivalence Principle. It has been argued that this violation implies that such a superposition must inevitably spontaneously collapse (like in the Diósi-Penrose model). We identify the origin of such an assertion in the impossibility of finding a local, classical reference frame in wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 27 publications
2
14
1
Order By: Relevance
“…The general idea employed here is to use the relativity of superpositions [23] under QRF transformations to make an indefinite metric definite. This aspect is similar to the one in previous works on QRFs for indefinite metrics [42,48], however there are important differences between the approaches. In [42,48], a local quantum inertial frame is introduced, which can be associated with a frame attached to a quantum particle falling freely in a superposition of gravitational fields.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…The general idea employed here is to use the relativity of superpositions [23] under QRF transformations to make an indefinite metric definite. This aspect is similar to the one in previous works on QRFs for indefinite metrics [42,48], however there are important differences between the approaches. In [42,48], a local quantum inertial frame is introduced, which can be associated with a frame attached to a quantum particle falling freely in a superposition of gravitational fields.…”
Section: Introductionsupporting
confidence: 76%
“…This aspect is similar to the one in previous works on QRFs for indefinite metrics [42,48], however there are important differences between the approaches. In [42,48], a local quantum inertial frame is introduced, which can be associated with a frame attached to a quantum particle falling freely in a superposition of gravitational fields. It was shown that in the transition to the local quantum inertial frame, the metric becomes Minkowskian, extending the validity of Einstein's equivalence principle to quantum reference frames and spacetimes in general superpositions.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Recently, it has led to a surge of interest in the quantum foundations community on the behavior of quantum systems under transformations between such "internal" quantum reference frames [30][31][32][33][34][35][36][37][38][39]. Among other results, this has led to proposals for quantum formulations of Einstein's equivalence principle [40][41][42][43][44] and to insights into the relativity of the notion of subsystem [45][46][47].…”
mentioning
confidence: 99%